2004
DOI: 10.1051/0004-6361:20031629
|View full text |Cite
|
Sign up to set email alerts
|

The structure of contact binaries

Abstract: Abstract. In radiative layers of rotating stars the luminosity carried by circulation currents through a surface of constant entropy (circulation luminosity) is shown to be positive. The corresponding decrease in the temperature gradient is important in the secondary of contact binaries. This result removes the deadlock in the theory of contact binaries. The resulting treatment of contact binaries is investigated, assuming thermal equilibrium. The sources of the circulation luminosity in the secondary can be w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…The spot parameters obtained from the solutions for both the binaries are shown in Table 3. Having a fill out factor of 21% for the star ID487 and 48% for the star ID494, and a small temperature difference between the components of about 13 K and 221 K in these two stars, it can be concluded that there is good thermal contact between the two components in both the systems and they are stable and least probable to merge (e.g., Kahler, 2004). The angle of inclination was found to be ∼ 63 o .5 for the binary ID487 and ∼ 68 o .4 for the binary ID494, indicating that both are partially eclipsing binaries.…”
Section: Discussionmentioning
confidence: 99%
“…The spot parameters obtained from the solutions for both the binaries are shown in Table 3. Having a fill out factor of 21% for the star ID487 and 48% for the star ID494, and a small temperature difference between the components of about 13 K and 221 K in these two stars, it can be concluded that there is good thermal contact between the two components in both the systems and they are stable and least probable to merge (e.g., Kahler, 2004). The angle of inclination was found to be ∼ 63 o .5 for the binary ID487 and ∼ 68 o .4 for the binary ID494, indicating that both are partially eclipsing binaries.…”
Section: Discussionmentioning
confidence: 99%
“…The evolution theories of these binary stars yield secular as well as shorter time scale quasi-cyclical orbital period variations. Although these theories suffer from a lot of problems their predictions can be used as guidelines (Kreiner et al 2003;Kähler 2004) to better understand the behaviour of these systems.…”
Section: Long-term Effectsmentioning
confidence: 99%
“…The classic W UMa question, however, is how they manage to spend large parts of their lives with two stars of different masses but very nearly equal surface temperatures. Kahler (2004) says it is done by a flow from the more massive star to the little one in their upper atmospheres and returning M 2 the favor deeper down, thereby flattening the expected temperature gradients. It can happen that both stars are spotted (Barnes et al 2004a) though we don't think the spots are carried back and forth.…”
Section: Types and Prototypesmentioning
confidence: 99%